Plastic use for food and drinks and related knowledge, attitudes, and practices among a sample of Egyptians - Fatma Mohamed Hassan; Eman D. El Desouky; Marwa Rashad Salem; Motaze Adel Abdelsabour; Mostafa Alaa Abdelmoneim; Mohamed Mahmoud Elsaieed; Mona Mohamed Ali; Mona Mohamed Ali (Frontiers in Public Health, 2023)
IntroductionPlastic is extensively used in everyday life, particularly for food and beverage containers. The inappropriate use of these containers may lead to the leaching of various chemicals from plastic, such as bisphenol A, phthalate, and styrene, which cause numerous adverse health effects. This study aimed to assess the knowledge, attitudes, and practices toward using plastic for food and drinks among a sample of the Egyptian population.Materials and methodsA questionnaire was designed based on scientific literature to assess sociodemographic data, knowledge, attitudes, and practices toward the use of plastic for food and drinks. A total of 639 participants were recruited by employing the convenience sampling technique.ResultsMore than half of the participants (347, 54%) had poor knowledge scores. Personal experiences, social media, and web pages represented the most common knowledge sources. A comparison between plastic-related knowledge scores and the studied sociodemographic characteristics revealed statistically significant differences in age, gender, education, marital status, residence, working, and socioeconomic standard. A good attitude was reported by the majority (515, 80.6%) of participants. The majority (493, 77.2%) were occasional and frequent plastic users and the practice scores were significantly associated with age, education, residence, and socioeconomic standard. Higher educational level, gender (women), and rural residence were predictors of good participants knowledge, while lower socioeconomic status and urban residence were predictors of bad participants practice in a multivariate logistic regression analysis.ConclusionThe observed unsatisfactory knowledge and practice scores vs. the high attitude indicates a knowledge gap that can help direct future improvements. We call for public awareness programs about safe plastic use and the related health hazards of plastic chemicals. We also stress upon the urgent need for a collaboration between health authorities and the plastic and food industry to guarantee that information about proper plastic use is conveyed to consumers.